1989
DOI: 10.1080/01652176.1989.9694191
|View full text |Cite
|
Sign up to set email alerts
|

Perineal hernia repair in the dog by transposition of the internal obturator muscle

Abstract: A modified technique for transposition of the internal obturator muscle was used to repair perineal hernias in 100 dogs. Complications and long-term results are described. The most important complications were wound infection (45%), faecal incontinence (15%), and perineal fistula (7%). These complications often occurred in combination. The recurrence rate of perineal hernia was 5%. Nine of the 15 patients with faecal incontinence had paresis of the external anal sphincter or faecal incontinence before surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 7 publications
4
34
1
4
Order By: Relevance
“…() who reported that 78% of their cases (all of which did not receive abdominal surgical interventions) were free of clinical signs 6 to 88 months after surgery. As previously reported, most of the complications developed within the first 3 months after surgery (Sjollema & van Sluijs , Shaughnessy & Monnet ). Three dogs still had persistent clinical signs related to PH>24 months after surgery.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…() who reported that 78% of their cases (all of which did not receive abdominal surgical interventions) were free of clinical signs 6 to 88 months after surgery. As previously reported, most of the complications developed within the first 3 months after surgery (Sjollema & van Sluijs , Shaughnessy & Monnet ). Three dogs still had persistent clinical signs related to PH>24 months after surgery.…”
Section: Discussionsupporting
confidence: 75%
“…, Shaughnessy & Monnet ). Recurrence rates are reported to range from 10 to 46% with primary herniorrhaphy, 0 to 33% with IOT and 10% when an abdominal procedure was combined with IOT in a two‐staged procedure (Sjollema & van Sluijs , Hosgood et al . , Brissot et al .…”
Section: Introductionmentioning
confidence: 99%
“…The recurrence rates have been reported from zero to 18.75% after TIOM [11,19,24,27,28], and zero to 12.5% after the use of a polypropylene mesh [9,26,28]. Principally, a surgeon should avoid the technique using foreign material when one utilizing the patient's own tissue is possible [28].…”
Section: Discussionmentioning
confidence: 99%
“…Among the techniques attempted to avoid reherniation, transposition of the internal obturator muscle (TIOM) is the most reliable technique and considered now the conventional herniorrhaphy. The transposed muscle increases strength of the ventral perineum where most hernias occur [11,19,24,27,28]. The reports on the herniorrhaphy utilizing other patient's own tissues for closing the defect include transposition of the superficial gluteal muscle [22,29], semitendinosus muscle [8] and fascia lata [5].…”
mentioning
confidence: 99%
“…Alternative techniques have been developed to improve hernial repair procedures and decrease the recurrence rate. Internal obturator muscle transposition (IOT) is currently the preferred surgical treatment (with recurrence rates between 2.4% and 19%), but repair can be difficult, particularly if the internal obturator muscle is atrophied [9,18]. Post-operative complications with the use of standard herniorrhaphy including IOT, and peripheral muscle autografts ( e.g.…”
mentioning
confidence: 99%